2018
DOI: 10.14202/vetworld.2018.909-914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various surgical procedures on biochemical parameters of Nigerian dogs and their clinical implications

Abstract: Aim:The importance of physical and psychological stress caused by pain during surgery cannot be overemphasized. The aim of this study was to assess the effects of ovariohysterectomy (OVH), gastrotomy (GST), and intestinal resection and anastomosis (IRA) on biochemical parameters of Nigerian dogs anesthetized with the xylazine-propofol combination.Materials and Methods:A total of 12 dogs were randomly divided into three groups of four each. The animals were treated with xylazine and propofol anesthetics for OVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In this study, plasma GLU increased at 60 min, remained elevated until 3 days, and decreased thereafter. Similar results have been documented in dogs undergoing OHE [ 12 , 47 ]. The maximum GLU levels in the latter studies were observed 1 h after anesthetic premedication, and levels were back to baseline after 24 h post-anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, plasma GLU increased at 60 min, remained elevated until 3 days, and decreased thereafter. Similar results have been documented in dogs undergoing OHE [ 12 , 47 ]. The maximum GLU levels in the latter studies were observed 1 h after anesthetic premedication, and levels were back to baseline after 24 h post-anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…Cardiovascular effects such as hypertension and tachycardia occur when catecholamines interact with the α 2 receptors that modulate the release of norepinephrine in the post-synaptic nerve endings as a result of epinephrine secretion in the adrenal medulla. This process affects the adenylyl cyclase system to increase cardiac contractility [26]. Finally, these receptors have been identified as components of the pain modulating pathway because the α 2 type can inhibit adrenergic impulses [25].…”
Section: Relationship Of Catecholamines To Surgical Stressmentioning
confidence: 99%
“…In the liver, glucocorticoids facilitate the ability to concentrate amino acids from extra-hepatic tissue (skeletal muscle) for subsequent degradation. This occurs because cortisol significantly enhances hepatic glutamic-pyruvic transaminase activity and subsequently increases the transamination of alanine to pyruvate and then lactate [26]. The release of catecholamines also increases the amount of pyruvate available for its later transformation into glucose [30].…”
Section: Cortisolmentioning
confidence: 99%
“…Ovariohysterectomy (OHE) is a common procedure for sterilization of female dogs [1,3,4]. The operation removes both ovaries, the uterine horns and the body of the uterus [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, if the stress response is prolonged, it results in longer hospitalization. Therefore, alleviating prolonged pain and stress in surgical patients is important for animal health [4]. The stress response is a physiological response to trauma or surgery and is generally considered to be proportional to the degree of surgical trauma [5].…”
Section: Introductionmentioning
confidence: 99%